Jeremiah, Joseph, and the Dynamics of Analogy On the Relationship between Jeremiah 37–44 and the Joseph Story - Teeter, Andrew 1976- (2021)
This study demonstrates how and why the depiction of the life of the prophet Jeremiah and his contemporaries in Jeremiah 37-44 displays systematic and thoroughgoing analogical correspondences to the Joseph Story in Genesis 37-50. These correspondences prove to represent a strategic part of a larger set of relationships to the Joseph Story found throughout the broader composition of the book of Jeremiah as a whole, as well as in the book of Kings. The present argument proceeds from a descriptive comparison of Jeremiah 37-44 and the composite Joseph Story, intended to provide an initial survey of the contours of this relationship and to serve as a foundation for detailed diachronic consideration elsewhere. The study concludes with reflections on the nature and function of analogical correspondence within this literature.